Efficient and secure data transmission: cryptography techniques using ECC - Alhaj, Abdullah Ahmad; Alrabea, Adnan; Jawabreh, Omar (Institute of Advanced Engineering and Science, 2024)
Data transmission has become a crucial aspect of our daily lives in the current digital age. However, this transmission comes with the risk of security breaches, which can result in data theft and unauthorized access. This issue can be addressed by using cryptographic techniques such as elliptic curve cryptography (ECC). In comparison to other cryptosystems, ECC is a potent cryptographic tool that provides high levels of security with comparatively reduced key sizes. This paper discusses the use of ECC in efficient and secure data transmission. It provides a comprehensive overview of ECC, including its mathematical background and how it can be applied to encryption and decryption processes. The paper also presents a comparison of ECC with other cryptographic techniques and highlights its advantages, including its resistance to attacks and efficiency in resource-constrained environments. Finally, the paper discusses the implementation of ECC in real-world scenarios and its potential to revolutionize secure data transmission.